Does Economic Policy Uncertainty Matter for Healthcare Expenditure in China? A Spatial Econometric Analysis - Bai, Pu; Tang, Yixuan; Zhang, Weike; Zeng, Ming (Frontiers in Public Health, 2021)
A growing body of research has documented the determinants of healthcare expenditures, but no known empirical research has focused on exploring the spatial effects of economic policy uncertainty (EPU) and healthcare expenditures. This paper set out to explore the spatial effects of EPU on healthcare expenditures using the panel data of 29 provinces in China from 2007 to 2017. Our findings have shown that healthcare expenditures in China have the characteristics of spatial clustering and spatial spillover effects. Our study also shows that EPU has positive spatial spillover effects on healthcare expenditures in China; that is, EPU affects not only local healthcare expenditures but also that in other geographically close or economically connected regions. Our study further indicates that the spatial spillover effects of EPU on healthcare expenditures only exist in the eastern region. Our empirical findings highlight the spatial spillover effects of EPU on healthcare expenditures.